The Impact of Self-Esteem, Social Support and Family Bonds on Elderly Female Happiness - Sharma, Tilak Prasad (Tribhuvan University Journal, 2024)
The increasing number of elderly people worldwide for a better understanding of the variables that promote their quality of life. In Nepal, advanced age women are subjected to unique enumerated socio-cultural and psychological elements that enhance detract from their happiness and life satisfaction. The objective of the present study is to assess self-esteem, social support and family bonding as predictors of happiness among elderly females, to provide information which assists in helping this group. A cross-sectional design was used and 133 elderly women formed the random sample using structural questionnaire. Results showed that the mean age of the respondent was 68.8, with the majority (61.7%) of the ages groups of 60- 69. Other remarkable results were that there was a high literacy level of 96.2 percent but a noteworthy 75.2 percent of the income was insufficiency. The self esteem and social support levels of the respondets were moderate; however, 56.7 percent of the respondents had chronic illness. The multiple regression analysis showed that self-esteem (Beta=0.477), social support (Beta=0.381), relations with family (Beta=0.124) proved to be powerful predictors of happiness accounting for 91.4 percent of the variance in life satisfaction. The findings of this study demonstrate the vital impact of self-worth, social network and family relations on the contentment of older females. This study showed that relationships and social support along with self-esteem have a great impact on elderly women's happiness. Quality of life for them could be increased dramatically by some intervention in these fields.